Queering Lactation: Contributions of Queer Theory to Lactation Support for LGBTQIA2S+ Individuals and Families. (May 2019) - Lee, Robyn
In this article I explore some contributions of queer theory to the provision of lactation support services. In doing so, I also undertake an intersectional analysis of queering lactation, recognizing that forms of oppression do not impact all individuals equally or in the same ways. While recognizing the history of tensions between queer and feminist politics and activism, I argue that queering lactation holds significant benefits for supporting lactation among LGBT families, as well as opening up possibilities for rethinking gender and possibilities for gender equality more generally.